2020
DOI: 10.1088/1361-6528/ab7e70
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-material dependence on the elongation of embedded gold nanoparticles induced by 4 MeV C60 and 200 MeV Xe ion irradiation

Abstract: We report the elongation of embedded Au nanoparticles (NPs) in three different matrices, i.e. amorphous carbon (a-C), crystalline indium tin oxide (InxSn1-xOz; ITO) and crystalline calcium fluoride (CaF2), under irradiations of 4 MeV C60+ cluster ions and 200 MeV Xe14+ ions. Under 4 MeV C60 cluster irradiation, strong sputtering is induced in CaF2 layer so that the whole the layer was completely lost at a fluence of 5 × 1013 ions cm−2. Au NPs were partly observed in the SiO2, probably due to the recoil implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…These results may be used as a starting point to understand seemingly incompatible experimental observations: elongation induced by individual impacts to NPs 4,31 but the overall process influenced by the embedding matrix 2,9,12 . The results show unambiguously that nearby impacts affect the stress within the NP, which changes the elongation rate.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…These results may be used as a starting point to understand seemingly incompatible experimental observations: elongation induced by individual impacts to NPs 4,31 but the overall process influenced by the embedding matrix 2,9,12 . The results show unambiguously that nearby impacts affect the stress within the NP, which changes the elongation rate.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, the first experimental investigations studying the dependence of the effect on the embedding matrix were reported 10,12 . We believe that our results will be important to interpret the experiments, as they show that the metal-matrix interactions affect the elongation rate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that different morphologies can be obtained based on the size of the initial sample by researchers at CNRS in Caen, France [35]. Precision aligned nanorods can be easily fabricated using swift heavy ion beam irradiation [36][37][38][39][40][41][42][43][44]. An investigation by the author and coworkers [45] examined the relationship between metal particle size and deposited energy.…”
Section: Introductionmentioning
confidence: 99%